(untitled) (Statistics, Optimization & Information Computing, 2025)
In this paper, we propose a new family of generalized distributions called the Topp-Leone type II Exponentiated Half Logistic-Marshall-Olkin-G (TL-TIIEHL-MO-G) distribution. The new distribution can be expressed as an infinite linear combination of exponentiated-G family of distributions. Some special models of the new family of distributions are explored. Statistical properties including the quantile function, ordinary and incomplete moments, stochastic orders, probability weighted moments, distribution of the order statistics and Renyi entropy are presented. The maximum likelihood method is used for estimating the model parameters and Monte Carlo simulation is conducted to examine the performance of the model. The flexibility and importance of the new family of distributions is demonstrated by means of applications to real data for censored and complete sets, respectively